If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + -64) = 56 Reorder the terms: 2(-64 + t) = 56 (-64 * 2 + t * 2) = 56 (-128 + 2t) = 56 Solving -128 + 2t = 56 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '128' to each side of the equation. -128 + 128 + 2t = 56 + 128 Combine like terms: -128 + 128 = 0 0 + 2t = 56 + 128 2t = 56 + 128 Combine like terms: 56 + 128 = 184 2t = 184 Divide each side by '2'. t = 92 Simplifying t = 92
| 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s | | -4b+20=-18-b-19 | | -10j=19-11j | | 5n-6=6n+11 | | 2(22-8)=22+6 | | (z^(-1/2)z^(5/2))/(z^(1/3)) | | 10+6-3r=-10+10r | | 12(12k+11)=12(12k+12) |